2016
DOI: 10.1002/asia.201501434
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Supramolecular Therapeutic Carriers Based on Host–Guest Interactions

Abstract: Recent advances in host–guest chemistry have significantly influenced the construction of supramolecular soft biomaterials. The highly selective and non‐covalent interactions provide vast possibilities of manipulating supramolecular self‐assemblies at the molecular level, allowing a rational design to control the sizes and morphologies of the resultant objects as carrier vehicles in a delivery system. In this Focus Review, the most recent developments of supramolecular self‐assemblies through host–guest inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 90 publications
(263 reference statements)
0
74
1
Order By: Relevance
“…As a drug delivery concept in nanotechnology, it strives to develop nanoscale materials for selective infusion of therapeutic drugs or pharmaceutical compounds to specific cells. It consists of submicron-sized colloidal particles such as nanoparticles, micelles, liposomes and vesicles [2]. These sophisticated materials have shown compelling results in their ability to transport a diverse range of pharmaceutical compounds to various parts of the human system including cells, tissues and organs for sustained periods of time [3][4][5].…”
Section: "Multiple Attempts Have Been Taken To Finetune Nanoparticlesmentioning
confidence: 99%
“…As a drug delivery concept in nanotechnology, it strives to develop nanoscale materials for selective infusion of therapeutic drugs or pharmaceutical compounds to specific cells. It consists of submicron-sized colloidal particles such as nanoparticles, micelles, liposomes and vesicles [2]. These sophisticated materials have shown compelling results in their ability to transport a diverse range of pharmaceutical compounds to various parts of the human system including cells, tissues and organs for sustained periods of time [3][4][5].…”
Section: "Multiple Attempts Have Been Taken To Finetune Nanoparticlesmentioning
confidence: 99%
“…[1][2][3][4] In this context, supramolecular assemblies of proteins with macrocyclic hosts are extremely interesting, both from the view point of its fundamental/mechanistic aspects and also on the details of its applied potentials. [1][2][3][4] In this context, supramolecular assemblies of proteins with macrocyclic hosts are extremely interesting, both from the view point of its fundamental/mechanistic aspects and also on the details of its applied potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Practically, the controlled release of guest molecules are attempted in response to various external stimuli such as temperature, pH, light, salt, enzymes, etc. [1,7] The development of such biocompatible, stimuli-responsive and controlled release nanoassemblies have become a prime focus in biomedical fields and also in in vivo applications. [6] A number of synthetic macrocyclic host molecules including cyclodextrins (CDs), cucurbit[n]urils (CBn), calixarenes (CXs), etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant advantage of viral vectors over other vector platforms is the high transfection efficiency in cells of quiescent and dividing status, previous studies reported that gene transfection was lower in these cell types, thus viral vectors were regarded to be optimal in certain applications . However, viral vector systems are not suitable for all applications . For instance, macrophage cells are resistant to the viral‐mediated gene transfection, and the administration of viral vectors easily induced immune response to produce proinflammatory cytokines and extensive toxicity in vivo .…”
mentioning
confidence: 99%